¿Es más costoso el transporte de carga por carretera que por el Río Magdalena? (2017)
At present, a comparative analysis is carried out between transport costs and a ton of freight by road and by the Magdalena River. First, the importance of each of these transport modalities is established, in order to estimate the characteristics or factors that contribute most to the variance of transport costs.